Homer’s vividness: an enactive approach - Grethlein, Jonas; Huitink, Luuk (The journal of Hellenic studies, 2017)
The vividness of Homeric poetry has been admired since antiquity, but has been difficult to pin down with precision. It is usually thought to come about because readers are prompted to visualize the storyworld in the form of mental images seen with the mind's eye. But this cannot be right, both because there are serious scientific problems with the concept of ‘pictures in the head’ and because Homer does not offer many detailed descriptions, which are a prerequisite for eliciting detailed mental images. This article presents a different, and cognitively more realistic, take on the imageability of Homeric epic, which is based on recent reader-response studies inspired by the enactivist theory of cognition. These studies make a compelling case for readerly visualization as an embodied response, which does not depend on bright or detailed mental images. An analysis of the chariot race in Iliad 23 identifies specific features of what may be called an ‘enactive style’, notably the description of simple bodily actions. The final part of the article demonstrates that an enactivist take on Homer's vividness is not incompatible with the ancient concept of enargeia, the chief rhetorical term with which Homer's vividness is characterized in ancient criticism.